Entrepreneurial skills for sustainable small business: An exploratory study of SCORE, with comparison. Issue 4 (8th August 2018) - Dahlstrom, Timothy R.; Talmage, Craig A.
ABSTRACT: Which skills must community members acquire and nurture to become successful local entrepreneurs in the communities in which they live and serve? Local small businesses are important community assets, and local wellbeing can be improved through entrepreneurship. Existing research shows only partial agreement on the skill dimensions that make up this required skillset, and a comprehensive skill framework has yet to surface. SCORE, a longstanding and successful US community economic development program, trains individuals in the skills necessary to start and successfully operate a small business. This article presents a qualitative, exploratory study of the skills developed through SCORE counseling that are associated with small business success. The SCORE skill dimensions are compared to a prominent practice-based model. The comparison reveals unique aspects of the SCORE skill dimensions not mirrored in other studies. Finally, this study opines how the study findings extend research regarding small business and community development.